STUDIES ON EFFECT OF ORGANIC MANURES AND BIOINOCULANTS ON VEGETATIVE AND FLORAL ATTRIBUTES OF CHRYSANTHEMUM CV. LITTLE DARLLING - BOHRA, MAMTA; KUMAR, AJIT (The Bioscan, 2014)
An investigation was conducted during 2010-2011, to study the effect of organic manures and bioinoculants on vegetative and floral attributes of chrysanthemum cv. Little Darling. The treatments comprising of VAM, Trichoderma sp. (each @ 20 g/plant), poultry manure, vermicompost (each @ 300 g/m2) and their combinations along with control. Among the treatments applied maximum plant height (30.17 cm), number of primary and secondary branches (3.78 and 19.78, respectively), plant spread (28.53 cm) and number of leaves per plant (184.33) were recorded in VAM (20 g/plant) + vermicompost (300 g/m2) at all stages of plant growth. With respect to flowering, application of VAM (20 g/plant) + vermicompost (300 g/m2) was found best as it resulted in bud initiation in minimum days (55.78), days to first flowering (73.33), maximum flowering duration (28.33 days), flower longevity (16.33 days), number of flowers per plant (70.56), flower stalk length (7.80 cm) and weight of flower (1.67 g). Maximum days taken to half of leaves (13.67) and flower wilting (17.17) were recorded in vermicompost (300 g/m2). Thus, it can be concluded from the findings that application of VAM (20 g/plant) + vermicompost (300 g/m2) can be recommended for commercial cultivation of chrysanthemum cv. Little Darling.